Development of Chatbot Learning Media on Earth Rotation and Revolution Materials for Grade 6 Elementary School Students - Nuri Seftiani Rosmiati*; Atep Sujana; Ani Nur Aeni (Universitas Syiah Kuala, 2023)
Difficulties are often found during the learning process. Therefore, learning media is very crucial in learning activities. With the existence of learning media can support teachers when providing learning to students. Chatbot learning media is one of the media that can help improve student learning outcomes. The purpose of this study was to find out and then describe the characteristics and analyze the truth pf increasing learning outcomes of grade VI students through the development of interactive print media in the material rotation and revolutation of earth. Researchers used the research and development (RD) method in this study. The 4D (four-D) development model previously described by Thiagarajan became the procedural model chosen by the researcher. The final score obtained in this study was 4.15 from media experts, 4.56 material experts, 4.8 teacher responses, and 4.58 student trial results. The overall validation score and trial of chatbot learning media is 4.58 which is included in the very good category and is very feasible to use as a learning media tool in grade 6